Physical Activity and Daily Steps Cut Offs Points for Overweight/Obesity Prevention Among Eight Latin American Countries - De Moraes-Ferrari, G (Nature Research, 2022)
This study aims to establish cut-off points for the number of minutes of physical activity intensity and the number of daily steps that identify overweight/obesity in adolescents, adults, and older adults. This study examined data from 2737 participants. Physical activity intensity and the number of daily steps were assessed using GT3X+ ActiGraph model accelerometers. Body mass index, waist-to-height ratio, and waist-to-hip ratio were used as indicators of overweight/obesity. The cut-off points for moderate-to-vigorous physical activity for the prevention of overweight/obesity according to body mass index in women ranged from 15.1 to 30.2 min/day; in men, the values were from 15.4 to 33.8 min/day. The lowest cut-off point for daily steps was established in the adolescent group for women and men (7304 and 5162). The highest value in women was 11,412 (51–65 years) and 13,234 in men (18–30 years). Results from measurements different from BMI, show average cut-off points for moderate-to-vigorous physical activity and daily steps of 29.1/8348 and 43.5/10,456 according to waist-to-height ratio; and results of 29.3/11,900 and 44.3/11,056 according to the waist-to-hip ratio; in women and men respectively. A more specific recommendation of physical activity and daily steps adjusted by sex and age range is suggested to prevent overweight/obesity. © 2022, The Author(s).